Cenas do espaço escolar: um convite a reolhar as práticas e suas aprendencias na educação para a cidadania - Bonfanti, Kátia (Universidade do Vale do Rio do Sinos, 2006)
This dissertation had the purpose of making studies on scenes of the school space, through the existence close to the managers, educators, students and community of School Flôres da Cunha, in the municipal district of Shore, Rio Grande do Sul. The project of the School, in their physical and political-pedagogic spaces, constituted the investigated central subject, as well as the relationship of these, with the construction of the citizenship. The verification was been worth of participant observation, questionnaires, semi-structured interviews and documents of the school, as PPP and the registrations done starting from the pieces of advice participant. Through the group of scenes analyzed in that dissertation, invited the interested reader to discuss the relationship of the scenes of the daily school, especially, the one of the external space, opposing to the established guidelines in the Pedagogic Political Project that it defined the actions, education conception and of citizenship in the school community
Keywords: comunidade; cidadania; emancipação; espaço escolar; cenas escolares; citizenship; community; emancipation; school scenes; space school; Ciências Humanas